THE ETHNOMATHEMATICS OF TUTUWARU COMMUNITY IN THE CRAFTS OF KOLI LEAF WEAVING - Laurens, Theresia; Kempa, Rudolf; Serpara, Henderika (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2020)
Ethnomatemics-based mathematics concept implementation can be carried out through constructivism-based learning such as realistic mathematics, problem-based and learning with a scientific approach. This research purpose to explore the form of ethnomatemics on the woven cabbage leaves of the Tutuwaru community and analyze the process of understanding mathematics from the perspective of indigenous people and indigenous knowledge and examine the development of woven form ethnomatatics in school mathematics. The method used in this research is descriptive qualitative research. The subjects are 2 members of the weaving community, while the objects of research are Nyiru (winnowing-basket), Topi (hat), Keranjang dan Bakul (basket). The results showed that the form of weaving from a typical local Koli (cabbage) tree, could be connected with several mathematical concepts such as basic geometry and arithmetic. The hexagonal concept based on the understanding of multiples is an